Trans-sodium crocetinate ameliorates Parkinson-like disease caused by bisphenol A through inhibition of apoptosis and reduction of α-synuclein in rats - Majid Keshavarzi; Bibi Marjan Razavi; Hossein Hosseinzadeh (Iranian Journal of Basic Medical Sciences, 2025)
Objective(s): Trans-sodium crocetinate (TSC) is one of the crocetin derivations that is more soluble and stable than crocetin and its cis form. It easily crosses the blood-brain barrier. TSC has neuroprotective effects. Bisphenol A (BPA) is an endocrine-mimicking compound that induces Parkinson-like disease by impacting the dopaminergic system. In this research, the effects of TSCs on BPA-induced Parkinson-like symptoms via behavioral and molecular assays have been investigated.Materials and Methods: Male Wistar rats received BPA (75 mg/kg, gavage), TSC (10, 20, and 40 mg/kg), and levodopa (L-dopa) (10 mg/kg) via intraperitoneal injection (IP) for 28 days. Parkinsonian-like motor features were evaluated using bar test, rotarod, and open field experiments. Malondialdehyde (MDA) and glutathione (GSH) levels were also measured as the most important indicators of oxidative stress. Western blotting was performed for the molecular assays of alpha-synuclein (α-syn), Bcl-2, Bax, caspase-3, Beclin, and LC3 I/II proteins. Results: Our analyses indicated that treatment with TSC at high dose reduces MDA levels and protects GSH reserves. TSC can also increase anti-apoptotic Bcl-2 and decrease pro-apoptotic Bax and Caspase-3 proteins. While it does not affect autophagy markers, TSC decreased α-syn protein expression, reduced the catalepsy time, and improved the time spent staying on the rotating bar and the locomotor activity.  Conclusion: Overall, TSC likely ameliorates BPA-mediated Parkinson’ s-like symptoms by suppressing oxidative stress inhibition. This leads to reduced α-syn expression, which ultimately results in apoptosis inductions. Therefore, TSC can serve as a promising exploratory target for future research aimed at controlling Parkinson’s disease.